Impact of Abdominal Follow-Up Sonography in Trauma Patients Without Abdominal Parenchymal Organ Lesion or Free Intraabdominal Fluid in Whole-Body Computed Tomography - Schneck, Emmanuel; Koch, Christian; Borgards, Mara; Reichert, Martin; Hecker, Andreas; Heiß, Christian; Padberg, Winfried; Alejandre-Lafont, Enrique; Röhrig, Rainer; Krombach, Gabriele Anja; Weigand, Markus; Bernhard, Michael; Roller, Fritz Christian (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2017)
Purpose Patients suffering from severe blunt abdominal trauma are challenging because of their need for accurate diagnostic imaging and fast therapeutic action. Whole-body computed tomography (WBCT) is highly sensitive and represents the gold standard in the trauma room diagnostic setting. The aim of our study was to investigate the impact and therapy relevance of abdominal follow-up sonography (AFS) as part of the tertiary trauma survey (TTS) in patients without abdominal parenchymal organ lesions or free abdominal fluid in initial WBCT.Materials and Methods All adult patients without abdominal parenchymal organ lesions or free intraabdominal fluid in the initial WBCT examination, who received AFS within 24 hours after trauma, were included in this retrospective analysis between January 2008 and December 2011.Results 316 patients were analyzed (ISS 10 ± 8, NISS 13 ± 11) according to the inclusion criteria. Overall, only small amounts of free intraabdominal fluid were detected in AFS in 3 patients (0.9 %) and remained without therapeutic consequence. None of the patients died due to intraabdominal bleeding.Conclusion AFS as part of the TTS did not show additional benefits and had no impact on further treatment in patients without abdominal parenchymal organ lesions or free intraabdominal fluid in the initial WBCT examination. We conclude that AFS is not routinely required but should be performed if indicated on a clinical or laboratory basis because of its fast and less invasive character.Key points Citation Format
Keywords: trauma; ultrasound; FAST; tertiary trauma survey